Kombinasi pendekatan lunak dan keras dalam mengatasi gejolak pemogokan buruh. - Syafaruddin Alwi (Universitas Islam Indonesia, 2001)
The phenomenon of labor strike for higher compensation during the 1996-2000 period is very important to be analyzed. The problem is why did they do it? This analysis is aimed to present how will the managers of companies reduce this strike actions.